Relevansi Al-Quran dalam Filsafat (Analisis Perilaku Masyarakat Tentang Hukum Kafaah) - Mida Mar`atus Sholihah; Ahmadi Hasan; Masyithah Umar (Sharia Journal and Education Center Publishing, 2023)
Abstract This research examines the meaning of kafaah in analysing people's understanding and behaviour related to kafaah. Much of previous studies related to religious kafaah is diverse, ranging from the meaning of kafaah as similarity in organisations, having the same memorising, even the same religious school or boarding school. The purpose of my research is to see what forms of behaviour from the community's understanding of kafaah, and to find out how the meaning of kafaah in the relevance between the relevance between al-Qur'an and philosophy. This research is a normative study with descriptive analysis. The method used in this paper is a literature study with research gap data collection techniques. The results of this study show that the meaning of kafaah religiously in society can mean similarities in education other than religious affairs, a religious environment, morals towards family and society, similarity of mass organisations, and special expertise in religion. In this case, the relevance of the Qur'an and philosophy related to the difference in the meaning of kafaah in society can be used as a diversity of kafaah treasures. So that there is no exclusion due to standards that are considered too high by the community. Keywords: Relevance, Behavior, Kafaah. Abstrak: Penelitian ini mengkaji makna kafaah dalam analisis pemahaman dan perilaku masyarakat terkait kafaah. Banyaknya kajian terdahulu terkait kafaah agama yang beragam, mulai dari makna kafaah sebagai kesamaan dalam berorganisasi keagamaan, memiliki hafalan yang sama, bahkan kesamaan sekolah agama atau pondokan. Tujuan penelitian ini melihat apa saja bentuk perilaku dari pemahaman masyarakat terkait kafaah, serta untuk mengetahui bagaimana makna kafaah dalam relevansi antara al-Qur`an dan filsafat. Penelitian ini merupakan kajian normatif dengan analisis deskriptif. Metode yang digunakan dalam tulisan ini yakni studi kepustakaan dengan tehnik pengumpulan data research gap. Hasil penelitian ini menunjukkan bahwa makna kafaah secara agama di masyarakat dapat berarti persamaan pendidikan selain urusan keagamaan, lingkungan yang agamis, akhlak terhadap keluarga dan masyarkat, kesamaan ormas, hingga keahlian khusus dalam beragama. Dalam hal ini relevansi al-Quran dan filsafat terkait perbedaan makna kafaah di masyarakat dapat dijadikan sebagai keberagaman khazanah kafaah. Sehingga tidak ada pengucilan akibat standar yang dinilai terlalu tinggi oleh masyarakat. Kata Kunci: Relevansi, Perilaku, Kafaah.